(untitled) (Bangladesh Journal of Botany, 2025)
An experiment was conducted to evaluate the effect of organic fertilizers and neem-coated urea on growth, yield, soil nutrient status and cost economics of sesame. Farmyard manure (FYM) @ 10 t ha⁻¹ significantly increased growth, with the highest test weight (2.87 g) and seed yield (349.4 kg/ha), followed by press mud cake @ 12.5 t ha-1 (M3). Among nitrogen treatments, 150% (S5) and 125% (S4) recommended dose of nitrogen (RDN) with neem-coated urea resulted in the highest seed yields (368.2 kg/ha and 353.4 kg/ha, respectively). The soil nutrient status showed increased nitrogen, phosphorus, potassium and organic carbon with organic amendments. Economic analysis revealed that M2S5 provided the highest net returns (₹20,258) and M3S5 exhibited the highest benefit-cost ratio (1.97). Thus, combining organic manures with neem-coated urea improves yield, soil health and economic returns in sesame. Bangladesh J. Bot. 54(4): 1069-1075, 2025 (December)